FACTORS AFFECTING COMPANY PROFIT DURING THE COVID-19 PANDEMIC AT PT. PASAR SWALAYAN MAJU BERSAMA. - Wijaya, Devita (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine and analyze the factors that affect company profits during the Covid-19 pandemic. This research uses quantitative data method and the source data is secondary data. The population in this study is the monthly report of PT. Pasar Swalayan Maju Bersama for 30 months (January 2020 to June 2022). Type the data in this study is secondary data sourced from financial statements. The sample in this study used a saturated sample of 30 months (January 2020 to June 2022) financial statements at PT. Pasar Swalayan Maju Bersama. Data analysis and testing consists of; descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (t test) and simultaneously (f test), and coefficient of determination test. The results of the t-test show that Sales have a significant effect on Net Profit, Input VAT has a significant effect on Net Profit, and Output VAT has a significant effect on Net Profit. The results of the F test show that Sales, Input VAT, and Output VAT have a significant effect on Net Profit.